Animals that travel - Urquhart, Jennifer C. ([Washington, D.C.] : National Geographic Society, 1982)
Text and illustrations describe animals that migrate in search of food and favorable conditions for survival.
card
Keywords: Animal migration -- Juvenile literature; Animals -- Migration